An oncolytic measles virus–sensitive Group 3 medulloblastoma model in immune-competent mice. Issue 12 (14th June 2018) - Lal, Sangeet; Carrera, Diego; Phillips, Joanna J; Weiss, William A; Raffel, Corey
Abstract: Background: Oncolytic measles virus (MV) is effective in xenograft models of many tumor types in immune-compromised mice. However, no murine cell line exists that is tumorigenic, grows in immune-competent mice, and is killed by MV. The lack of such a model prevents an examination of the effect of the immune system on MV oncotherapy. Methods: C erebellar stem cells from human CD46-transgenic immunocompetent mice were transduced to express S endai virus C-protein, murine C -Myc, and G fi1b proteins. The resultant cells were injected into the brain of NSG mice, and a cell line, called CSCG, was prepared from the resulting tumor. Results: CSCG cells are highly proliferative, and express stem cell markers. These cells are permissive for replication of MV and are killed by the virus in a dose- and time-dependent manner. CSCG cells form aggressive tumors that morphologically resemble medulloblastoma when injected into the brains of immune-competent mice. On the molecular level, CSCG tumors overexpress natriuretic peptide receptor 3 and gamma-aminobutyric acid type A receptor alpha 5, markers of Group 3 medulloblastoma. A single intratumoral injection of MV‒green fluorescent protein resulted in complete tumor regression and prolonged survival of animals compared with treatments with phosphate buffered saline ( P = 0.0018) or heat-inactivated MV ( P = 0.0027). Conclusions: This immune-competent model provides the first platform to test therapeutic regimens of oncolytic MV for Group 3 medulloblastoma in the presence of anti-measles immunity. The strategy presented here can be used to make MV-sensitive murine models of any human tumor for which the driving mutations are known.